Correlation of temperature-sensing microchip and rectal temperature measurements in cats - Goig, Marta; Godino, Javier; Tejedor, Maria Teresa; Burgio, Federica (Frontiers in Veterinary Science, 2024)
Rectal temperature (RT) is the reference standard for clinical evaluation of body temperature in mammals. However, the use of a rectal thermometer to measure temperature can cause stress and other problems, especially in cats. There is a need for clinical techniques that reduce both stress and defensive behavior as part of the provision of better medical care. Subcutaneous temperature-sensing identification microchips fulfil the current legal requirements and provide a reading of subcutaneous temperature (MT). The clinical study tried to determine whether there is agreement between MT and RT in normal (n=58), hospitalized (n=26) and sedated/anesthetized (n=36) cats. Three measurements were taken using both methods (MT and RT) in each cat. Correlation between MT and RT, and differences between MT and RT, were estimated for pairs of data-points from the same individual, and all data pairs in each group were considered overall. There was a strong positive correlation between MT and RT (r= 0.7 to 1.0) (P<0.0005). The mean differences (d) were always negative and although statistically significant, these d values are likely of no biological importance. The overall d was -0.1ºC in normal cats (P<0.0005), -0.1ºC in hospitalized cats (P=0.001) and -0.1ºC in sedated/anesthetized cats (P=0.001). The limits of agreement between MT and RT appear narrow enough for MT to be acceptable estimate of RT. The overall limits of agreement (95%) were -0.71ºC and 0.53ºC (in normal cats); -0.51ºC and 0.34ºC (in hospitalized cats) and -0.60ºC and 0.42ºC (in sedated/anesthetized cats). MT may provide a good alternative to RT measurement in cats. However, this study was mostly performed in animals that were normothermic. Therefore, further studies in larger groups of cats under different conditions are needed to compare trends and assess variation with time.